2016
DOI: 10.1098/rstb.2015.0088
|View full text |Cite
|
Sign up to set email alerts
|

Models of social evolution: can we do better to predict ‘who helps whom to achieve what’?

Abstract: Models of social evolution and the evolution of helping have been classified in numerous ways. Two categorical differences have, however, escaped attention in the field. Models tend not to justify why they use a particular assumption structure about who helps whom: a large number of authors model peer-to-peer cooperation of essentially identical individuals, probably for reasons of mathematical convenience; others are inspired by particular cooperatively breeding species, and tend to assume unidirectional help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 123 publications
(210 reference statements)
0
22
0
Order By: Relevance
“…Reciprocity, the third potential cause of correlated pay-offs, is arguably the most contended possibility to generate cooperation and altruism [12,32]. It is the theme of this article and a focus of many contributions to this special issue of the Philosophical Transactions [7,[33][34][35][36][37].…”
Section: Correlated Pay-offsmentioning
confidence: 97%
“…Reciprocity, the third potential cause of correlated pay-offs, is arguably the most contended possibility to generate cooperation and altruism [12,32]. It is the theme of this article and a focus of many contributions to this special issue of the Philosophical Transactions [7,[33][34][35][36][37].…”
Section: Correlated Pay-offsmentioning
confidence: 97%
“…The evolution of social behaviour in a demographic context has received a substantial amount of attention over the past few years (Lehmann and Rousset , Rodrigues and Kokko ). To a large extent, however, this work assumes that local habitats have an infinite lifespan, whereby patches are perpetually colonised, have an endless supply of resources, and are immune to ecological disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Above, I have considered that dispersal was a fixed model parameter. Sometimes, this may be an implausible assumption, as dispersal often changes with local environmental conditions, in general, and with patch age, in particular, as observed in many species (Crespi and Taylor , Roff , Korb and Lenz , 2005, Clobert et al 2009, , Ronce and Clobert , Aguillon and Duckworth ) and suggested by multiple theoretical studies (Crespi and Taylor , Roff , Olivieri et al 1995, 2005, Kisdi et al , Rodrigues and Johnstone , Rodrigues and Gardner ). To investigate this biological scenario, I now consider that production of public goods co‐evolves with the dispersal of individuals.…”
Section: Model and Methodologymentioning
confidence: 99%
See 2 more Smart Citations